The History of Materials Management: Quality Management from a Cameroon Perspective - Tata, Daniel Tabeng; Antoinette, Yuh (ExcelingTech, 2026)
Materials management and quality management are critical for organizational efficiency and national economic development, especially in Cameroon, where their evolution has been shaped by colonial influences, economic reforms, and globalization [1]. This review explores the development of these disciplines in sectors such as agriculture, oil, and manufacturing, drawing on global and regional literature and practical case studies. The integration of quality management systems such as Total Quality Management (TQM), Six Sigma, and ISO standards has promoted continuous improvement and customer satisfaction [2]. Influential figures like Walter Shewhart, W. Edwards Deming, and Joseph Juran laid the foundations for modern quality practices, with Japan emerging as a leader in TQM by the 1960s [3]. Despite the widespread adoption of QMM in developed regions, Cameroonian organizations still face challenges related to implementation, customer satisfaction, and adapting to local market needs [4].The study offers recommendations for policymakers and business leaders aiming to advance sustainable growth and operational excellence in Cameroon and similar emerging.